2017
DOI: 10.29210/02018190
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat Kecanduan Internet pada Remaja Awal

Abstract: <p>This study shows that there are students who have an Internet addiction. Addictions possessed by students will certainly have a negative impact on self, social relationships and learning outcomes. This study aims to describe: 1) The level of Internet addiction in general 2) The core symptoms of Internet addiction in early adolescents 3) Problems related to Internet addiction in early adolescence. Quantitative research method with the quantitative descriptive approach. The population of this study is 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
25

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 9 publications
0
18
0
25
Order By: Relevance
“…A study of IA in five Asian countries (China, Hong Kong, India, South Korea, and Taiwan) reported a 7.1% prevalence rate, which was slightly higher than the worldwide average (Cheng & Li, 2014). The Indonesian prevalence rate has also been reported as being between mild and medium; however, no specific percentages have been reported (Sari, Ilyas, & Ifdil, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…A study of IA in five Asian countries (China, Hong Kong, India, South Korea, and Taiwan) reported a 7.1% prevalence rate, which was slightly higher than the worldwide average (Cheng & Li, 2014). The Indonesian prevalence rate has also been reported as being between mild and medium; however, no specific percentages have been reported (Sari, Ilyas, & Ifdil, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Despite the convenience, there is also a threat, such as the impact on the younger generation. Research has shown the negative sides of the Internet use on children if not monitored and controlled [1][2][3][4]. Research shows that most teenagers spend 1 to 8 hours per day on the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…Internet traffic payload trends and patterns between active school days (as) and semester break (sb) The percentage of difference/delta in this section is referred to as delta B as shown in(2), which compares the difference in usage between as and h based on the time period. Internet traffic payload trends and patterns between active school days (as) and initial fasting holiday (ifh) The percentage of difference/delta in this section is referred to as delta C as shown in(3), which compares the difference in usage between as and ifh based on the time period.…”
mentioning
confidence: 99%
“…This research shows that there are 164.8 million smartphone users actively accessing the internet. The high level of smartphone use makes individuals vulnerable to smartphone addiction; this is because smartphone use has a significant effect on smartphone addiction (A. P. Sari, Ilyas, & Ifdil, 2017). The individual's self-control also influences the intensity in behaving over himself.…”
Section: Introductionmentioning
confidence: 99%